Advocacy as a Human Rights Enabler for Parents in the Child Protection System - Maylea, Chris (2023)
Parents and guardians in child protection systems are in unequal power relationships with child protection practitioners. This relationship is experienced as exclusionary or even oppressive by many parents and guardians. For families and communities in the child protection system who experience intersectional discrimination and disadvantage, such as people with intellectual disabilities and First Nations people, this unequal relationship and subsequent potential exclusion and oppression can be even more profound. A growing body of literature indicates that advocacy can assist in addressing unequal relationships in other contexts, such as involuntary mental health. This paper explores the role of representational advocacy in supporting parents in child protection settings through a case study of an advocacy service in Victoria, Australia. Using a human rights framework to guide the analysis, the paper highlights how advocacy can help support rights, but that broader structural change will be required to consistently uphold the rights of parents.